Review on Colloidal Quantum Dots Luminescent Solar Concentrators. Issue 20 (24th May 2021) - Kim, Andrew; Hosseinmardi, Alireza; Annamalai, Pratheep K.; Kumar, Pawan; Patel, Rajkumar
Abstract: Luminescent solar concentrators (LSCs) have recently gained popularity as an effective solution to increase solar energy conversion. Utilizing LSCs together with solar cells can generate more energy at a lower cost than using only solar cells. LSCs operate by utilizing luminophores, molecules that absorb incident solar irradiation and re‐emit photons, and waveguides that redirect emitted photons to the edges of a glass or polymer slab at high concentrations. Many quantum dots (QDs) have been the focus of much research as luminophores for LSCs, owing to their high quantum yields (QYs), controllable absorption/emission spectra, good stability, and ease of synthesis. Various QDs, such as CdSe, PbS, CdS, AgInS2, Si, and C, have been modified to enhance their optical performances in LSCs, often measured by their optical efficiencies, internal/external quantum efficiencies, and power conversion efficiencies. This review appraises the latest developments in colloidal QDs—basic QDs, doped QDs, core/shell QDs, hybrid QDs, and Si‐based QD—for their applications in LSCs. Other factors that enhance an LSC's efficiency, such as altering the polymer matrix and using distributed Bragg reflectors, are discussed. The development of highly efficient, QD‐based LSCs will be essential for increasing solar energy production worldwide.  Abstract : Luminescent solar concentrators can break through current solar energy limitations by making photovoltaics accessible in crowded urban cities and efficient in massive solar farms. Recent advances in basic, doped, core/shell, hybrid, and Si‐based quantum dots have improved the absorption, re‐emission, and stability of these luminophores. With the latest quantum dot designs boasting high energy efficiencies and long‐term stability, the advent of luminescent solar concentrators in modern photovoltaic systems is imminent.